Immunologic approaches for the treatment of lymphoid malignancies : from concept to practice - O'Connor, Owen A.; Ansell, Stephen M.; Gribben, John; Ohio Library and Information Network (Hoboken, NJ : Wiley Blackwell, 2023)
"Optimizing an effective antitumor immune response has always been the goal of immunological strategies to treat cancer. It has been known for many years that the immune system plays a central role in cancer development and control; and promoting the immune response may be of profound therapeutic value. Patients with evidence of immunosuppression are at higher risk for cancer and while spontaneous remissions in certain cancers are uncommon, they are a well-recognized phenomenon. Additionally, there are reports of patients whose malignancy regressed at the time of an infectious episode suggesting that activation of the immune system promoted an anti-tumor effect. Furthermore, many indolent lymphomas follow a 'waxing and waning' course suggesting that the immune system may modulate progression of the disease. Understanding the components of an effective antitumor immune response, and developing strategies to optimize them, has led to remarkable advances in the treatment of cancer, particularly lymphoid malignancies. Some of the key steps in this process are highlighted below and the various components of immunotherapy in use to treat patients are discussed in the chapters that follow"--
Includes bibliographical references and index
Keywords: Cellular immunity; Lymphoma -- immunology; Lymphoma -- therapy; Immunotherapy -- methods; Immunoconjugates -- therapeutic use; Immunity, Cellular